Collaborative GovernanceIn Overcoming Unemployment in Bengkalis Regency, Riau Province - Herman, Herman; Kartius, Kartius; Abdullah, Syapril; Hasibuan, Caissy Rahmadhani (PERSPEKTIF, 2024)
The purpose of this research is to analyze and explain the implementation of Collaborative Governance in Overcoming Unemployment in Bengkalis Regency, Riau Province. This research uses a qualitative method with descriptive research type. Techniques in determining informants with purposive sampling. The type of data source consists of two, namely primary and secondary data. For data collection techniques used are by prioritizing interview techniques, observation and documentation. The data analysis technique that the author uses is by collecting data which is then analyzed in depth and concluded as a whole in order to get the results of collaborative governance in tackling unemployment. The results in this study concluded that there is still a lack of collaboration between stakeholders in tackling unemployment due to the lack of company involvement in activities carried out by the Bengkalis Regency Government, including job fairs and workforce training. It is hoped that in the future the Bengkalis Regency Government can give an appeal to companies to be actively involved in participating in programs to reduce unemployment and evaluate these activities optimally.